Normalized training loss vs. baselines (Facebook). - Hossein Rafieizadeh (22676722) (2025)
DCOR reports both reconstruction-only and total (with RLC); baselines report reconstruction-only. Each curve is normalized as in Eq (29) by dividing by its epoch-1 value and EMA-smoothed (exponential moving average) with , where the EMA is computed as with . This normalization enables fair visual comparison across methods with different objectives and scales; the plot therefore emphasizes relative convergence trends (shape and stability) rather than raw magnitudes. Consistent with DCOR’s design, RLC regularizes late-phase training: the reconstruction curve decreases more conservatively than methods that minimize reconstruction alone, while the total objective continues to decrease.